If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6x + 7(2x + 6) = 142 Reorder the terms: -6x + 7(6 + 2x) = 142 -6x + (6 * 7 + 2x * 7) = 142 -6x + (42 + 14x) = 142 Reorder the terms: 42 + -6x + 14x = 142 Combine like terms: -6x + 14x = 8x 42 + 8x = 142 Solving 42 + 8x = 142 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-42' to each side of the equation. 42 + -42 + 8x = 142 + -42 Combine like terms: 42 + -42 = 0 0 + 8x = 142 + -42 8x = 142 + -42 Combine like terms: 142 + -42 = 100 8x = 100 Divide each side by '8'. x = 12.5 Simplifying x = 12.5
| -90-6x=48-12x | | -100=n+8 | | 7x+5(4-2x)=5 | | (8x+4)(8x-4)=y | | -4(-3x-8)-4x+8= | | (x-35)+90+43=180 | | 6(p+8)= | | -90-6x=48-12x | | -4(-3x-8)-4x+8= | | 6(p+8)= | | x+28500-y=371500 | | 6(p+8)= | | x+28500-y=371500 | | 15/30=6/x | | 7x=3(3x-4) | | 7x=3(3x-4) | | 7x=3(3x-4) | | 175*20+25= | | -4=2/3m+6 | | -6x+7(-2x+6)=142 | | x+28500-x=371500 | | -4[p+1]=-2[8-2p] | | p+26.3=12.74 | | 18-50= | | v/4-2=8 | | x+28500-x=371500 | | -16+3x=x+4x | | p+26.3=12.74 | | x+28500-x=371500 | | -6x+7(-2x+6)=142 | | [(2x-45-20)2]-5=0 | | 18-50= |